PENYULUHAN GAYA HIDUP SEHAT UNTUK JIWA YANG KUAT - Intan Pujilestari; Dini Rohmayani; Rizqy Dimas Monica (ASOSIASI IDEBAHASA KEPRI, 2023)
In a healthy body there is a strong soul. Perhaps we have heard the sentence called for in an activity. This certainly does not escape the healthy lifestyle that must be applied. We can start a healthy lifestyle from the family environment. Starting from diet, rest patterns, hygiene and exercise. The problem that often arises in people in Indonesia is usually the lack of maintaining a diet, so that the body feels physically unwell resulting in diseases that are owned by the community. Rest patterns also affect the health of our bodies, as a result we will feel excessive fatigue. Uncomfortable environmental cleanliness will bring about diseases around the environment. Irregular exercise then our bodies do not feel fit. Based on the problems described above, community service aims to provide counseling on a healthy lifestyle for a strong soul. As a result of the dedication that has been carried out for the residents of Taman Bukit Cibogo RT 08, the residents are very happy with the counseling held by the service team, so that residents get useful knowledge and can apply a healthy lifestyle to their daily lives.